The prevalence of cardiovascular disease by vascular bed and impact on healthcare costs in a large, real‐world population with type 2 diabetes. Issue 2 (20th January 2020) - Weng, Wayne; Kong, Sheldon X.; Ganguly, Rahul; Hersloev, Malene; Brett, Jason; Hobbs, Todd; Baeres, Florian M.M.
Abstract: Introduction: The purpose of this study was to assess prevalence of atherosclerotic cardiovascular disease (ASCVD) according to number of affected vascular beds and the impact on healthcare utilization and costs in persons with type 2 diabetes mellitus (type 2 DM) and established ASCVD. Methods: In this retrospective, cross‐sectional analysis, adults with type 2 DM and ASCVD in a large US administrative claims database were categorized by number of ASCVD‐affected vascular beds (brain, heart, peripheral vasculature). Annual healthcare utilization and costs for 2015 were determined, including subgroup analyses by age group (18‐44, 45‐64, ≥65 years). Results: Among 539 089 individuals with type 2 DM and ASCVD, 47.0% had ASCVD affecting >1 vascular bed. The most prevalent ASCVD diagnoses were acute coronary syndrome (26.6%), peripheral arterial disease (24.5%) and stroke (18.6%). Mean annual total healthcare costs per person increased with increasing number of vascular beds, from 1 ($17 741) to 2 ($25 877) to 3 ($33 412). A similar pattern of increased healthcare utilization with increasing number of vascular beds was observed. Among individuals with 1 affected vascular bed, mean total healthcare costs per person were comparable across age subgroups; however, if >1 vascular bed was affected, the mean total healthcare costs were highest in the youngest age cohort. Conclusions: These real‐world data showed that almost half of individuals with type 2 DM and ASCVD had ASCVD affecting >1 vascular bed. A higher number of affected vascular beds were associated with higher mean total healthcare costs and utilization, with a disproportionate increase noted in younger relative to older people. Abstract : There are limited data regarding the healthcare cost impact of ASCVD based on the number of affected vascular beds. This analysis, using claims data from 539 089 individuals with type 2 DM and ASCVD, found that 47.0% (n = 253 548) had ASCVD affecting >1 vascular bed, and a higher number of affected vascular beds were associated with higher mean total healthcare costs. These findings underscore the economic burden of ASCVD in people with type 2 DM, particularly among those with multiple affected vascular beds.